Durabilitas Laston dengan Filler Abu Gambut - Yuniarto, Enno; Sentosa, Leo (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
Bituminous mixtures to represent mixture used to roadway pavement. The bituminous mixtures generally consist of aggregate, filler and asphalt upon which fastener. Material used occasionally as filler are Portland cement, fine sand, stone ash and lime stone dust. which are its limited supply and also costly relative. The other alternative, usage Peat fly ash from industrial disposal or waste of paper mill fuel. Laston required good basic properties are stability, flexibility, skid and durability. To know the reliability of durability from Laston used peat fly ash as filler by The Marshall Immersion modified durability test. Durable Index expressed by IRS and Durable Index of Craus. From laboratory test Laton mixture with filler of peat fly ash assign value IRS equal to 95.22% at 28 day immersion, First Craus Durable Index (r) value equal to 1.73% and also Second Craus Index (a) equal to 4.22 %. If compared to condition assess minimum IRS from Bina Marga for the Laston, which is 75%, IRS Laston value with Palm Ash filler up to Bina Marga standard value.Keywords: filler, industrial waste, peat fly ash, laston, durabilityPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3945[How to cite: Yuniarto, E. dan Sentosa, L., 2006, DurabilitasÂ  Laston dengan Filler Abu Gambut, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 189-197]